The Physiological Impact of Window Murals on Pediatric Patients. (April 2019) - Pearson, Michelle; Gaines, Kristi; Pati, Debajyoti; Colwell, Malinda; Motheral, Leslie; Adams, Nicole Gilinsky
Objectives: To examine the magnitude of impact of two nature-themed window murals on physiological processes, as measured by heart rate and blood pressure, of pediatric patients. Background: Many children and adolescents find at least one aspect of the hospitalization process frightening or anxiety provoking. One physical feature linked to stress reduction is access to positive distractions. Views of nature are one of the most common forms of positive distractions in healthcare environments. Patient room windows are the most common way patients are exposed to natural elements. Exposure to views of nature is linked to a number of positive impacts on physiological outcomes. Unfortunately, not every patient room will be able to provide a nature-filled window view. In situations where nature scenes do not occur, enhanced nature views may be utilized to replicate many of the same benefits as actual nature views. Methods: Pediatric patients were randomly assigned to one of the three room conditions: aquatic window mural, tree window mural, or control condition. The medical data of participants ( n = 90) who stayed in the rooms were gathered and evaluated for differences. Results: Data analysis supports the notion that patient stress is heightened at the time of admission. Patients in the rooms with murals were found to have improvements in heart rate and systolic blood pressure in comparison to patients in control rooms, suggesting that the murals had an impact on physiological processes. Data also suggest that subject matter played a role, as patients in tree murals rooms had the most health-related outcomes.